Green supply chain strategy considering participant fairness concern and uncertainty of research and development - Haohao Song; Rong Wang; Xiangyu Mao; Jing Tao; Mengqi Zhang; Xiaobo Wang; Xiaojuan Sang (Scientific Reports)
Abstract Considering the uncertainty of green technology research and development (R&D) investment and channel members’ fairness concern behavior, this article respectively analyzes participants’ optimal decision-making under the manufacturer-dominated and the retailer-dominated structures. Given the probability of high efficiency and low efficiency of green R&D, this article uses the expected values under different probabilities to represent the equilibrium results. Through numerical simulations, we further comparatively discuss the equilibria under different scenarios. The results indicate that regardless of whether the manufacturer’s green R&D is efficient or inefficient, it always will lead to an increase in products’ pricing, greenness, demand, retailer’s profit, and supply chain’s social welfare. However, the change in the manufacturer’s profit is uncertain, which is also related to its fixed R&D costs and R&D efficiency. Under the manufacturer-dominated structure, fairness concern behavior can lead to a decrease in products’ pricing, greenness, demand, and profits for both the manufacturer and retailer; But under the retailer-dominated structure, the manufacturer’s fairness concern has no impact on products’ retail price, greenness, and demand. It only leads to the retailer raising markup price and reducing marginal profit, while the manufacturer’s wholesale price and profit will increase. In addition, whether under the manufacturer-dominated and the retailer-dominated structures, the supply chain’s social welfare is greater than that without green R&D and increases with the increase of the probability of efficient R&D. Nevertheless, the impact of the manufacturer’s fairness concern on social welfare is not the same. It leads to a decrease in social welfare under the manufacturer-dominated structure, while leads to an increase under the retailer-dominated structure.